Botulism and tetanus - Thwaites, C (Elsevier, 2017)
Botulism and tetanus are diseases caused by neurotoxins produced by Clostridium botulinum and Clostridium tetani, respectively. The bacteria and the toxins they produce are closely related. Both diseases are rare in the UK and the developed world, but tetanus, in particular, is a major cause of death in the developing world, causing between 100,000 and 200,000 deaths each year. In botulism a descending flaccid paralysis occurs, whereas in tetanus generalized muscle spasms develop. Autonomic nervous system dysfunction can occur in either disease, and in tetanus cardiovascular parameters can fluctuate widely. Early involvement of respiratory muscles means that rapid recognition and prompt institution of supportive measures are important in improving survival.